Controlled loading response cemented backfill support for deep tabular stopes - Lamos, August Wilhelm (My University, 1993)
Hydraulically placed cemented backfill is increasingly being used as a means of stope support in South African hard-rock mines. The addition of binder provides backfill with a primary compressive strength. the property for which the material has traditionally been utilised. Binder-induced cohesion, however, is not the only factor determining the quality of cemented backfill and the material's utility can be enhanced significantly by applying all of its attributes to the task of stope support. The main purpose of this thesis is, therefore, to examine those factors which influence the performance of cemented backfill, and to provide relevant and useful information for the design of improved cemented backfill mine support for tabular mining excavations. In an extensive laboratory investigation, a number of relevant factors were tested for their influence on the loading behaviour of cemented backfill. Twenty two cemented backfills. grouped according to aggregate type, water content, binder content and binder type, were analysed to determine the influence of composition on their material properties. This study was augmented by several test series on the effects of curing conditions on cemented backfill quality. In a second major investigation, the effects of geometrical parameters, including sample volume and sample width to height ratios were analysed. A further study dealt with the effect of spatially separating sample backfill ribs under normal compression, as well as at high closure rates. It is concluded, that by co-ordinating the composition design of cemented backfills with the spatial configuration of backfill support elements, it is possible to modify all phases of the cemented backfill loading response. This implies the control of the binder-induced compressive strength at low strains, the large-scale yielding behaviour of backfill support, as well as the stiffness of the backfill body at high stresses. In the light of stope support requirements. particularly under rockburst conditions, the capacity of backfill support to yield and absorb rapid stope closure and then to decelerate the hangingwall by the rapid strain-hardening of the, now, large width to height ratio backfill mass, has the potential of substantially increasing mine safety in tabular stopes,
A thesis submitted to the Faculty of Engineering, University of the Witwatersrand. Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy
Keywords: Concrete mine supports.; Stoping (Mining); Mine filling.; Dynamic testing.